Public understanding and evaluation of information related to obesity health risks in Sweden and Malaysia - Hashim, Azirah; Azman Firdaus, Aliyyah Nuha Faiqah; Lindström, Nataliya Berbyuk; Ahlsén, Elisabeth; Rodin, Pavel; Yee, Chee Leong; Attaran, Ali; David, Maya Khemlani; Allwood, Jens (AEI Insights, 2021)
This study examines and compares the awareness of weight-related issues of Swedes and Malay Malaysians, as well as attitudes to health risks related to being obese and preferences for and evaluation of different information channels. A questionnaire was distributed to respondents from these two socio-culturally distinct countries and the responses were analyzed using descriptive statistics. The findings of the study show both similarities and differences between Swedes and Malay Malaysians. Respondents in both countries show an awareness of where to turn to for information and the health problems linked to obesity. Both similarities and differences are found in preferences for information sources and usefulness of information. In the Swedish data, social media, family and friends and expert talks were considered both easy to understand and trustworthy and the information obtained from these sources is evaluated as very useful while blogs were seen as easy to understand but not trustworthy. In the Malaysia data, blogs, Youtube/Vimeo and social media are considered the easiest to understand but less likely to be trustworthy. In both countries, public health care institutions and governmental agencies are rated as trustworthy, but low in understandability. In Malaysia, expert talks to the public and private institutions are also seen as trustworthy. Daily newspapers, leaflets, radio/TV, and alternative medicine is seen as neither easy to understand nor trustworthy by the respondents in both countries. The outcomes of this study provide insights into the obesity attitudes of Swedes and Malaysians and their preferences for information sources. The results can contribute towards better understanding of cultural influences in the planning of health services in both countries.